2016
DOI: 10.1371/journal.pone.0150957
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dissolved Oxygen during UV-Irradiation on the Chemical Composition and Function of CHO Cell Culture Media

Abstract: Ultraviolet (UV) irradiation is advantageous as a sterilization technique in the biopharmaceutical industry since it is capable of targeting non-enveloped viruses that are typically challenging to destroy, as well as smaller viruses that can be difficult to remove via conventional separation techniques. In this work, we investigated the influence of oxygen in the media during UV irradiation and characterized the effect on chemical composition using NMR and LC-MS, as well as the ability of the irradiated media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…As the biopharmaceutical industry progresses to disposable production equipment, UV technology could be well disposed to provide a sterile, disposable disinfection system. The authors of the present review have been using a family of prototype reactors in which the wetted part consists of disposable Teflon, and the design has been scaled from internal volumes of 27-500 mL [70] with corresponding increases in flow. The same design could be readily scaled further, achieving a range of disposable UV reactors suitable for perfusion, or for parallel batch production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the biopharmaceutical industry progresses to disposable production equipment, UV technology could be well disposed to provide a sterile, disposable disinfection system. The authors of the present review have been using a family of prototype reactors in which the wetted part consists of disposable Teflon, and the design has been scaled from internal volumes of 27-500 mL [70] with corresponding increases in flow. The same design could be readily scaled further, achieving a range of disposable UV reactors suitable for perfusion, or for parallel batch production.…”
Section: Discussionmentioning
confidence: 99%
“…Keywords Biopharmaceutical · Adventitious agent · Ultraviolet · Irradiation · Disinfection · Viral clearance 1 3 because of the lack of available literature on the topic. Recently, an effort to correct this has been undertaken and our group has published research considering the effect of UV fluence on the composition and function of cell culture media [70,117].…”
Section: Introductionmentioning
confidence: 99%
“…Biomolecules such as glucose, lactate, and amino acid (Schmidt et al, 1998 ; Roychoudhury et al, 2007 ; Fan et al, 2016 ) are important nutrients or metabolites in biomanufacturing. Environmental parameters such as pH, dissolved O 2 or CO 2 also play pivotal roles on the growth of cell culture media (Meunier et al, 2016 ; Michl et al, 2019 ). Monitoring of those major targets during cell culture cultivation is of great value for the regulation and management of biological production.…”
Section: Major Targets In Biomanufacturing Monitoringmentioning
confidence: 99%
“…UV-C irradiation has been used in the biopharmaceutical industry for the treatment of blood products such as purified plasma proteins and blood clotting agents [15,16], and has shown great potential in the inactivation of many pathogens, including non-enveloped viruses such Hepatitis A and parvovirus [17,18]. Furthermore, we previously reported on a UV-C continuous flow disinfection system that has the potential to achieve industry required standards for sterility of cell culture media [19]. Given the complexities and diversity of cell culture media however, there is a need for a deeper understanding of the potential deleterious effects that UV-related reactions can have on essential cell culture media components.…”
Section: Introductionmentioning
confidence: 99%
“…UV irradiation of cell culture media can result in formation of hydrogen peroxide (H 2 O 2 ), which is a reactive oxygen species (ROS) that can start free radical reactions causing oxidation of fatty acids and amino acids, and enzyme deactivation, leading to diminished growth and cell death [21]. Previously, we have shown that although high doses of UV-irradiation can lead to decreased cell growth and viability [19], moderate doses result in damage more akin to daylight exposure [13]. It has been speculated by others that the generation of H 2 O 2 during UV irradiation plays a major role in the destruction of several media components, via reactions with tryptophan and riboflavin, leading to poor cell growth [22].…”
Section: Introductionmentioning
confidence: 99%